Othonella araguaiana (Bivalvia, Megadesmidae) from the Corumbataí Formation (Midlle Permian), Eastern Margin of the Paraná Basin: Systematic, Evolutionary and Biostratigraphic Significances - Marcello Guimarães Simões; Luiz Eduardo Anelli; Juliana Machado David (Geologia USP. Série Científica, 2010)
In this study, the occurrence of Othonella araguaiana Mendes, a rare bivalve species is reported for the first time in thePinzonella illusa biozone, Middle Permian Corumbataí Formation, in the State of São Paulo. This species was originallydescribed in coeval rocks of the Estrada Nova Formation (= Corumbataí) from the Alto Araguaia and Alto Garças regions,State of Mato Grosso. The specimens of O. araguaiana were found in the base of a bioclastic sandstone bed, a proximaltempestite, in the middle of the Corumbataí Formation, in the city of Rio Claro, São Paulo State. The silicified shells andinternal molds are well preserved, showing impressions of muscle scars and other internal anatomic characters (e.g., hinge),never illustrated by previous authors. In his original description, Mendes (1963) called attention to the similarity betweenO. araguaiana and Terraia aequilateralis, a common veneroid of the Corumbataí Formation. Conversely, Runnegar andNewell (1971) suggested that O. araguaiana belongs to Megadesmidae, being a junior synonym of Plesiocyprinella carinata(the commonest megadesmid of the Passa Dois Group). Our study indicates that O. araguaiana is indeed a megadesmid,but is distinct from the P. carinata. The new occurrence of O. araguaiana demonstrates that a) the paleobiogeographicdistribution of this species is wider than previously thought (that it was restricted to the northern part of Paraná Basin,Mato Grosso State); b) the molluscan fauna of the Corumbataí Formation (P. illusa biozone) in the State of São Paulo ismore diverse and dominated by megadesmids; and c) the composition of the molluscan fauna of the Corumbataí Formationin Alto Garças, State of Mato Grosso, is essentially the same as that of the P. illusa biozone of the eastern margin of theParaná Basin.